(untitled) (Al-Qamar, 2021)
Earlier it was said that knowledge is a wealth that cannot be stolen. No bandit can steal it. But in modern times where technology has progressed and the acquisition of knowledge has become easier thanks to computers and internet. At the same time, a type of academic, literary and moral corruption has also been made easy through which knowledge, literature and ideas can be stolen. This is called plagiarism. The definition of plagiarism is "to pass off another person’s writing or idea as your own, or to present it in such a way that it appears to be the author’s." Literary plagiarism is not a new thing, but it has been going on for a long time, but it has come to the fore in the modern era. Materialism has also been introduced. Under Western law, any academic or literary work is owned by its author. And printing it without his permission is a violation of his right. And for the violation of this right, punishments have been set in the context of copyrights (printing rights). According to these laws, one’s writing cannot be printed without his permission. There is also a fixed amount of taking copies (photostats) of this writing, making more copies is also a crime. Its purpose is that one’s The writing cannot be sold by another person. Likewise, copy to someone’s idea is also plagiarism by using your own words and publishing them under your own name, and translating someone else’s writing under your own name is also called literary plagiarism.In the era of Hadith, while computers and the Internet have made it easier for the common man to access knowledge, these modern facilities have also made plagiarism easier and its paraphrasing is also easy. Many people and organizations are taking advantage of this facility. These diseases are rapidly flourishing in our country and are affecting the quality of higher education along with research and editing. Our literature and journalism are badly affected by plagiarism. In my article I ll try to present details of plagiarism, its position in Quran O Sunnah and how to control it.